Timelines of Transportation Infrastructure Delivery 2000 to 2018 in Toronto, Canada and London, UK - Shoshanna Saxe; Marco Dean; Shivani Raghav; Dan Durrant; Matti Siemiatycki (European Journal of Transport and Infrastructure Research, 2021)
This paper explores the timelines of large transportation infrastructure delivery, from first proposal to construction and opening in London, UK and Toronto, Canada. The goal of the paper is to identify both how long it takes projects to go from idea to delivery, the relative time of different stages in the delivery process, and if projects with long timelines see physical or technological changes in their design. This work contributes to two ongoing discussions around the speed of infrastructure delivery, one that argues infrastructure moves too slowly and major efforts are needed to speed delivery and another that argues that good infrastructure thinking requires time to breathe and care should be taken in rushing through the delivery process. Detailed delivery timelines from initial proposal to construction or operation are developed for 26 transportation projects (16 in Toronto and 10 in London) between the years 2000 and 2018. For each project the timelines of inception, approval, planning, procurement, environmental assessment, construction and operational phases are identified and compared. Long informal gestation periods are identified for many projects, particularly for linear projects. In many instances the informal gestation period dwarfs the time projects spent in formal planning. This research highlights the need to expand the conception of timeliness of infrastructure delivery to include the lengthy periods of informal debate and planning that can span years and build up community expectations about the imminence of a project, even before it has received formal assessment or approval. Detailed delivery timelines from initial proposal to construction or operation are developed for 26 transportation projects (16 in Toronto and 10 in London) between the years 2000 and 2018. For each project the timelines of inception, approval, planning, procurement, environmental assessment, construction and operational phases are identified and compared. Long informal gestational periods are identified for many projects, particularly for linear projects. In many instances the informal gestation period dwarfs the time projects spent in formal planning. This research highlights the need to expand the conception of timeliness of infrastructure delivery to include the lengthy periods of informal debate and planning that can span years and build up community expectations about the imminence of a project, even before it has received formal assessment or approval.